Abstracts of the 6th International Academic Medical Congress of Maranhão (VI COIMAMA) 2019 - IJMS Executive Committee of IJMS (University Library System, University of Pittsburgh, 2020)
Abstracts of the 6th International Academic Medical Congress of Maranhão (VI COIMAMA) 2019